EXCELLENT NURSING CARE MANAGEMENT SERVICES FOR MRS.F WITH SUICIDE RISK AT PROF. Dr. MUHAMMAD ILDREM MENTAL HOSPITAL, MEDAN, NORTH SUMATRA PROVINCE, IN 2025 - Zuraini, Putri; Isyos Sari Sembiring; Indra Agussamad; Darwis; Laura Gultom; Begtaria Oktavia Simamora; Desi Ratnasari (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Suicide risk is a critical complication among patients with psychiatric disorders, particularly those diagnosed with hebephrenic schizophrenia. This study aims to delineate the implementation of psychiatric nursing care integrated with service excellence principles for Mrs. F, a patient at high risk for suicide at Prof. Dr. Muhammad Ildrem Mental Hospital, Medan. Case study design was employed, with data triangulated through clinical observation, in-depth interviews, and medical record documentation. The initial assessment revealed profound hopelessness, perceived worthlessness, social withdrawal, and a documented history of suicidal behavior. The established nursing diagnoses were Suicide Risk, Risk for Self-Directed Violence, and Chronic Low Self-Esteem. Interventions focused on service excellence through structured relaxation training, cognitive restructuring to bolster self-worth, and the fortification of adaptive coping mechanisms. Following a three-day intensive implementation, evaluation results demonstrated a significant reduction in suicidal ideation and an enhanced capacity for emotional regulation. A psychiatric nursing care model rooted in service excellence effectively mitigates suicide risk and optimizes the quality of life for patients with complex mental disorders